2021
DOI: 10.1183/16000617.0340-2020
|View full text |Cite
|
Sign up to set email alerts
|

Natural variability in the disease course of SSc-ILD: implications for treatment

Abstract: Interstitial lung disease (ILD) affects approximately 50% of patients with systemic sclerosis (SSc) and is the leading cause of death in SSc. Our objective was to gain insight into the progression of SSc-associated ILD (SSc-ILD). Using data from longitudinal clinical trials and observational studies, we assessed definitions and patterns of progression, risk factors for progression, and implications for treatment. SSc-ILD progression was commonly defined as exceeding specific thresholds of lung function worseni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 85 publications
1
9
0
1
Order By: Relevance
“…Variation of disease course is well known in SSc, where patients can have a rapid progression, stability of disease, and even improvement. Our data confirmed that most patients’ lung function remained stable over the 2-year period; some of them even improved similarly to the Scleroderma Lung Study (SLS) I and II trials and SENSCIS ( Volkmann et al, 2017 ), ( Vonk et al, 2021 ).…”
Section: Discussionsupporting
confidence: 78%
“…Variation of disease course is well known in SSc, where patients can have a rapid progression, stability of disease, and even improvement. Our data confirmed that most patients’ lung function remained stable over the 2-year period; some of them even improved similarly to the Scleroderma Lung Study (SLS) I and II trials and SENSCIS ( Volkmann et al, 2017 ), ( Vonk et al, 2021 ).…”
Section: Discussionsupporting
confidence: 78%
“…Another significant cardiopulmonary complication accounting for additional high mortality is pulmonary hypertension (PH) [ 3 , 4 ]. The clinical course of this disease shows a high variability in progression [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…SSc-ILD has a variable natural history [ 20 ]. Some patients have relatively stable disease for a prolonged period, while others develop a progressive phenotype characterized by worsening fibrosis on HRCT, progressive decline in lung function, worsening dyspnea, and an increase in mortality [ 3 ].…”
Section: Progression and Monitoring Of Ssc-ildmentioning
confidence: 99%